Prevalence, dynamics and characteristics of forced marriage in Spain - Villacampa Estiarte, Carolina (Crime, law and social change, 2020)
Forced marriages were criminalized in Spain in 2015, both as a specific form of coercion (offence against liberty) and as a type of human trafficking. However, the criminalisation was carried out with limited data on existing cases and without empirical research questioning whether forced marriages were taking place in Spain and what specific individuals were at risk. This paper presents the main findings of an empirical study aimed at detecting the existence of victims of forced marriage in this country and at describing the dynamics and characteristics of the processes which led to their victimisation. A total of 150 support organizations operating in Spain reported their knowledge of the extent and dynamics of forced marriages, revealing the existence of people forced to marry against their will, including some legal residents and even Spanish nationals. The research identifies at least 57 victims who have received assistance from support organizations. People most at risk were very young women, usually from North African, Sub Saharan African or Central Asian, as well as, to a lesser extent, Roma, and with a large percentage of Spanish nationals and legal residents. Mechanisms used to compel the victims are usually subtle, far from those more incisive active means required in the Spanish legislation. The results contribute to the debate on what is tolerable in today’s globalized society and underscore the need to understand this reality before regulating it.